2017
DOI: 10.1097/mbc.0000000000000564
|View full text |Cite
|
Sign up to set email alerts
|

Home treatment of haemarthrosis with recombinant activated factor VII in patients with haemophilia A or B and inhibitors

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Individuals with haemophilia A with inhibitors were the predominant population across the included studies, accounting for 76% to 100% of all participants. Individuals with haemophilia B with inhibitors accounted for 4% to 24% . The study by Bech et al also included a minority of participants with acquired haemophilia or FVII deficiency, and one individual in Santagostino 1999 had acquired haemophilia A.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Individuals with haemophilia A with inhibitors were the predominant population across the included studies, accounting for 76% to 100% of all participants. Individuals with haemophilia B with inhibitors accounted for 4% to 24% . The study by Bech et al also included a minority of participants with acquired haemophilia or FVII deficiency, and one individual in Santagostino 1999 had acquired haemophilia A.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen of the included studies reported data for FVIII inhibitor titres. Across eight of these studies, the mean values for inhibitor titre ranged from 8.6 BU/mL to 200.8 BU/mL (ADEPT ™ 1; data on file). The median inhibitor titre reported in two studies was 18 and 19 BU/mL, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5] Meanwhile, home treatment of haemophiliacs is the standard of care in developed countries and gets increasingly implemented also in developing countries as it has a positive impact on patients' health-related quality of life (HRQoL). 4,6 In the United States, approximately 70% of patients with haemophilia receive individualized care by a HTC. 7 Across Europe, the availability of HTCs and the range of services provided by different centres vary significantly between different countries.…”
Section: Introductionmentioning
confidence: 99%